(3eaGJjM GdTaG aj GdJYQja HMbhb GdoeUWais - (3CHhRjO GdaGSj , YHO GdQMef Hf YHO GdbGOQ Hf Ydj Hf CHj GdeMGSf jhSa GdaGSj,J (B1096 (3g` s
(3ChdgG (B:s
(3aUd ai cdGe GdTLQ hTgGOJgG dg HGdfHhI s
(3BNQgG (B:s
(3abGd YHOGddg (B: (3gi MQe Gddg hHjJg aCTjQ Edi YHOGddg aGfUQa GfJgi eG hLO ef eHjVI eDdag QVi Gddg Yfg YGe KdGKI hNeSjf heGFI hCda s
(3ef GdfSNI faSgGs
(3haj GdUaMI GdChdi HYV JedcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B145s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B525 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B410 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs